Pengaruh Model Pembelajaran Kooperatif Tipe Tgt Berbantuan Media Educaplay Terhadap Hasil Belajar Ipas Kelas V SDN 060970 Bagan Deli - Patresia Situmorang; Robenhart Tamba; Wildansyah Lubis; Imelda Free Unita Manurung; Yusra Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to investigate the effect of cooperative learning model Team Games Tournament (TGT) with Educaplay media on science learning outcomes of fifth-grade students at SDN 060970 Bagan Deli. The study employed a quantitative method with a Quasi-Experimental design using pretest and posttest with non-equivalent control-group design. The research subjects were 56 fifth-grade students at SDN 060970 Bagan Deli, selected through purposive sampling technique. Based on the research results, the data analysis showed a significance value (2-tailed) of 0.000 < 0.05. The hypothesis was accepted based on the t-test where t-hitung = 4.524 > t-tabel = 1.673, resulting in the rejection of H0 and acceptance of Ha. The mean score in the control class was 70.53, while the experimental class achieved a mean score of 80.36. The effect size calculation using Cohen's d formula yielded a value of 1.206, which is interpreted as a large effect size. Therefore, it can be concluded that the cooperative learning model TGT with Educaplay media has a significant effect on improving the learning outcomes of fifth-grade students at SDN 060970 Bagan Deli.